Analisis Bunyi pada Budaya Gedogan Masyarakat Osing Banyuwangi - Rahmania, Ulya Ghifrani; Handayani, Rif’ati Dina; Maryani (Universitas Nurul Huda, 2023)
Gedogan is one of the arts that can be found in several places in Banyuwangi. Gedogan is part of the culture of pounding rice from the Osing Banyuwangi community. This is a musical art that is played by women using a mortar and pestle that are smacked against each other. This study aims to analyze the sounds that appear in the Gedogan. Data were collected by interview, observation, and documentation. Data were analyzed using software (software) Visual Analyzer (VA) which can detect sounds along with the intensity and frequency of incoming sounds. This research illustrates that the sound in Gedogan depends on the material of the mortar, its size, position, and the point of impact. This can be seen from different measured sound frequencies. The Gedogan Rumah Wisata Osing group distinguishes sounds with the techniques of othek 1, othek 2, and othek 3. The frequency produced in the games of the Gedogan Rumah Wisata Osing group ranges from 320-1120 Hz This study is expected that this research will be a way to preserve culture by introducing and integrating related learning.